STUDI PENGARUH REKONFIGURASI LOOP SCHEME TERHADAP KEANDALAN PENYULANG BLAHKIUH DAN PENYULANG PANGLAN - yoga, bagus widyananda; Arjana, I Gede Dyana; Pemayun, A.A Gede Maharta (Jurnal Teknologi Elektro; Vol 17 No 1 (2018): (Januari - April) Majalah Ilmiah Teknologi Elektro, 2017)
Abstract —To improve reliability, the do loop system reconfiguration scheme to Blahkiuh feeders and feeders Panglan, by analyzing the calculation SAIFI and SAIDI, can the economy in terms of pressing / kWh minimize the number of unsold losses. Analysis of calculation results Blahkiuh feeders and feeder reconfiguration Panglan before result Blahkiuh feeder SAIFI 16.534 times/customers/year and the results SAIDI 35.894 hours/customer/year so the numbers of unsold kWh losses from the calculation not save 227,640.841 kWh energy equivalent to Rp 318,718,182.6, while for the results obtained Panglan feeder SAIFI 23.59 times/customer/year, the results of SAIDI 87.39 hours/ customer/year and the calculation results energy not save 238,037.099 kWh equivalent to Rp 364,672,835.7. After reconfiguration can minimize the number of SAIFI / SAIDI and losses, the results obtained Blahkiuh feeder SAIFI 2,089 times/ customers/year and the results SAIDI of 4.27 hours/customer/year, results energy not save 13369.314 kWh equivalent to Rp 20,481,733.86. For Panglan feeder SAIFI results obtained 1,218 times/customers/year and the results SAIDI 1,242 hours/ customer/year, results energy not save 3880.571 kWh equivalent to Rp 5,945,033.22.   I ntisari — Untuk meningkatkan keandalan maka dilakukan rekonfigurasi sistem loop scheme pada penyulang Blahkiuh dan penyulang Panglan, dengan menganalisa perhitungan SAIFI dan SAIDI , ditinjau dari segi ekonomi mampukah menekan/ memperkecil angka kerugian kWh yang tidak terjual. Hasil Analisa perhitungan penyulang Blahkiuh dan penyulang Panglan sebelum rekonfigurasi diperoleh hasil SAIFI penyulang Blahkiuh 16,534 kali/pelanggan/tahun dan hasil SAIDI 35,894 jam/pelanggan/tahun sehingga angka kerugian kWh tidak terjual dari hasil perhitungan energy not save 227.640,841 kWh setara dengan Rp 318.718.182,6, sedangkan untuk penyulang Panglan diperoleh hasil SAIFI 23,59 kali/pelanggan/tahun, hasil SAIDI 87,39 jam/pelanggan/tahun dan hasil perhitungan energy not save 238.037,099 kWh setara dengan Rp 364.672.835,7. Setelah rekonfigurasi dapat memperkecil angka SAIFI/SAIDI dan kerugian yang dialami, pada penyulang Blahkiuh didapat hasil SAIFI 2,089 kali/pelanggan/tahun dan hasil SAIDI 4,27 jam/pelanggan/tahun, hasil energy not save 13.369,314 kWh setara dengan Rp 20.481.733,86. Untuk penyulang Panglan didapat hasil SAIFI 1,218 kali/pelanggan/tahun dan hasil SAIDI 1,242 jam/pelanggan/tahun, hasil energy not save 3.880,571 kWh setara dengan Rp 5.945.033,22.   Kata Kunci : Sistem radial , Loop scheme , SAIFI/SAIDI , Energy not save [Turnitin Chek 12% 13042017]